Health records as the basis of clinical coding: Is the quality adequate? A qualitative study of medical coders' perceptions. Issue 1 (January 2020) - Alonso, Vera; Santos, João Vasco; Pinto, Marta; Ferreira, Joana; Lema, Isabel; Lopes, Fernando; Freitas, Alberto
Background: Health records are the basis of clinical coding. In Portugal, relevant diagnoses and procedures are abstracted and categorised using an internationally accepted classification system and the resulting codes, together with the administrative data, are then grouped into diagnosis-related groups (DRGs). Hospital reimbursement is partially calculated from the DRGs. Moreover, the administrative database generated with these data is widely used in research and epidemiology, among other purposes. Objective: To explore the perceptions of medical coders (medical doctors) regarding possible problems with health records that may affect the quality of coded data. Method: A qualitative design using four focus groups sessions with 10 medical coders was undertaken between October and November 2017. The convenience sample was obtained from four public hospitals in Portugal. Questions related to problems with the coding process were developed from the literature and authors' expertise. The focus groups sessions were taped, transcribed and analysed to elicit themes. Results: There are several problems, identified by the focus groups, in health records that influence the coded data: the lack of or unclear documented information; the variability in diagnosis description; "copy & paste"; and the lack of solutions to solve these problems. Conclusion and implications: The use of standards in health records, audits and physician awareness could increase the quality of health records, contributing to improvements in the quality of coded data, and in the fulfilment of its purposes (e.g. more accurate payments and more reliable research).